Scaling properties of normal faults in the central Afar, Ethiopia and Djibouti: Implications for strain partitioning during the final stages of continental breakup. (October 2018) - Polun, Sean G.; Gomez, Francisco; Tesfaye, Samson
Abstract: The central Afar depression offers an opportunity for quantitative analysis of the final stages of continental breakup at a divergent triple junction. Here, Quaternary faulting dissects Plio-Pleistocene flood basalts, providing a regionally pervasive datum to quantify the regional finite strain and fault scaling laws. To this end, we mapped and measured more than 8500 normal faults using remote sensing products. Fault length generally follows a power law distribution, but exponential distributions are found in areas of magmatic extension. Fault throw and fault length scale following a power law relationship where T = 0.031 L 0.96, similar to previous studies in Afar and elsewhere in the world. Combining the power law distribution with this throw scaling enables a comprehensive assessment of Quaternary finite strain throughout the region. Strain is greatest near Manda Inakir, Lake Asal, and the Dobe-Hanle accommodation zone. The Makarassou fault zone shows low strain, suggesting it does not kinematically link the Manda Inakir and Asal rift segments. The presence of moderate to high strain in the amagmatic portions of the central Afar rift suggests that those areas accommodate a significant proportion of plate motion. This may provide a future path for propagation between the Gulf of Aden Rift and the Red Sea Rift. Highlights: Fault length and displacement scaling laws for the central Afar are evaluated. Fault length mostly follows power law; exponential distributions also observed. Finite strain analysis suggests the Makarassou fault zone is not a kinematic link. High strain areas may provide future path of magmatic propagation.